Causes and Effects of Employee Stock Option Plans: Evidence from Singapore - DING, David K. (Institutional Knowledge at Singapore Management University, 2001)
This study highlights the determinants for the adoption of employee stock option plans (ESOPs) in Singapore and measures the impact of ESOP announcements on the shareholder wealth of adopting companies. We find that ESOP value is positively associated with a firm's growth opportunities but negatively related to interest coverage. Although larger firms are more likely to adopt ESOPs relative to smaller ones, among those that use ESOPs, the larger firms tend to use less ESOPs than the smaller ones. A further investigation of the market response to the adoption of ESOPs shows that the stock price reacts positively to such announcements, suggesting that investors view ESOPs favorably. The evidence demonstrates that ESOPs tend to align managerial with shareholder interests and contribute to the improvement of company performance.